2014
DOI: 10.1093/occmed/kqu097
|View full text |Cite
|
Sign up to set email alerts
|

Animal allergen sensitization in veterinarians and laboratory animal workers

Abstract: Animal workers are at high risk of occupational sensitization to animal allergens. Exposure should be minimized through control measures and worker education about the risks of exposure and sensitization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
2
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 25 publications
0
7
2
1
Order By: Relevance
“…2). These results are in clear contrast to the empirical studies of animal workers in laboratory or in stables [1,4], in which animal workers or riders have a greater possibility to be-come allergic against horses due to contact with these animals. The results of our study demonstrate that chronic contact to Curly horses does not induce an increasing risk of developing a stronger allergic reaction in nose, lungs or skin.…”
Section: Peak Expiratory Flow and Lung Function Measurementscontrasting
confidence: 91%
“…2). These results are in clear contrast to the empirical studies of animal workers in laboratory or in stables [1,4], in which animal workers or riders have a greater possibility to be-come allergic against horses due to contact with these animals. The results of our study demonstrate that chronic contact to Curly horses does not induce an increasing risk of developing a stronger allergic reaction in nose, lungs or skin.…”
Section: Peak Expiratory Flow and Lung Function Measurementscontrasting
confidence: 91%
“…Some studies have identified asthmatic workers by self-report questionnaires of symptoms. 30,31 An advantage of the present study Skin symptoms data from twenty-one subjects were missing. PR, prevalence ratio; CI, confidence interval.…”
Section: Resultsmentioning
confidence: 96%
“…Some studies have identified asthmatic workers by self‐report questionnaires of symptoms . An advantage of the present study was the identification of BHR by bronchial challenge test with mannitol, an indirect stimulation agent .…”
Section: Discussionmentioning
confidence: 98%
“…Most animal allergens belong to mammals and birds, which are easily spread into the environment [5-7]. Sensitization to cockroaches is among the most common factors contributing to increased asthma morbidity.…”
Section: Introductionmentioning
confidence: 99%